Association Between Symptom Burden and Physical Function in Older Patients with Cancer. Issue 5 (8th March 2019) - Pandya, Chintan; Magnuson, Allison; Flannery, Marie; Zittel, Jason; Duberstein, Paul; Loh, Kah Poh; Ramsdale, Erika; Gilmore, Nikesha; Dale, William; Mohile, Supriya G.
Abstract : OBJECTIVES: To evaluate the independent association between symptom burden and physical function impairment in older adults with cancer. DESIGN: Cross‐sectional. SETTING: Two university‐based geriatric oncology clinics. PARTICIPANTS: Patients with cancer aged 65 years or older who underwent evaluation with geriatric assessment (GA). MEASUREMENTS: Symptom burden was measured as a summary score of severity ratings (range = 0‐10) of 10 commonly reported symptoms using a Clinical Symptom Inventory (CSI). Functional impairment was defined as the presence of one or more impairments of instrumental activities of daily living (IADLs), any significant physical activity limitation on the Medical Outcomes Survey (MOS), one or more recent falls in the previous 6 months, or a Short Physical Performance Battery (SPPB) score of 9 or less. Multivariate analysis evaluated the association between symptom burden and physical function impairment, adjusting for other clinical and sociodemographic variables. RESULTS: From 2011 to 2015, 359 patients with cancer and a median age of 81 years (range = 65‐95 y) consented. The mean CSI score was 23.2 ± 20.5 with an observed range of 0 to 90. Patients in the highest quartile of symptom burden (N = 91; CSI score 52 ± 13) had a higher prevalence of IADL impairment (91% vs 51%), physical activity limitation (93% vs 65%), falls (55% vs 21%), and SPPB score of 9 or less (92% vs 69%) (all P values <.01) when compared with those in the bottom quartile (N = 81; CSI score: 2 ± 2). With each unit increase in CSI score, the odds of having IADL impairment, physical activity limitations, falls, and SPPB scores of 9 or less increased by 4.8%, 4.4%, 2.9%, and 2.5%, respectively ( P  < .05 for all results). CONCLUSIONS: In older patients with cancer, higher symptom burden is associated with functional impairment. Future studies are warranted to evaluate if improved symptom management can improve function in older cancer patients. J Am Geriatr Soc 67:998–1004, 2019.